Prepared for transition? A cross‐sectional descriptive study of the gains attained in early psychosis programs. Issue 5 (14th January 2020) - McCay, Elizabeth; Tibbo, Philip; Conrad, Gretchen; Crocker, Candice; Langley, John; Kirwan, Nicole; Aiello, Andria; Danaher, Audrey; Sheasgreen, Clare
Abstract: Aim: To examine the degree to which youth identified as ready for discharge from three Canadian early psychosis intervention (EPI) programs had achieved optimal outcomes (ie, symptom remission, quality of life, self‐esteem and functioning). Methods: This cross‐sectional descriptive study is part of a larger study assessing the effectiveness of an evidence‐based intervention to sustain the gains acquired in EPI programs in two Canadian provinces (Ontario and Nova Scotia), as youth transition from EPI services to community‐based care. Baseline data collected from 39 participants receiving usual treatment in these three EPI programs comprised the comparison group. Participants completed measures to assess symptoms, quality of life, self‐esteem and functional level just prior to discharge. Results: Participants demonstrated lower levels of symptoms, greater quality of life, greater self‐esteem and greater levels of functioning, following EPI treatment when compared to similar youth described in the literature. These findings suggest that study participants had achieved optimal outcomes following EPI treatment. Conclusion: The study findings have laid the ground work for the current Canadian Institutes of Health Research partnership study in which our research group is assessing the effectiveness of an evidence‐based transitional intervention in order to address critical psychosocial issues of identity, stigma, effective relationships and meaningful life goals, along with the development of an individualized 'passport for transition'. It is anticipated that implementing an evidence‐based transitional intervention will support participants to maintain the gains made in EPI programs once they transition to community‐based care and will inform future research addressing this challenging issue.